Mini Nutritional Assessment for Adult Cancer Patients: A Systematic Review and Meta-Analysis. (13th December 2022) - Wang, Pengpeng; Jiang, Li; Soh, Kim Lam; Ying, Yanping; Liu, Yuanhang; Huang, Xueling; Tan, Yanmei; Soh, Kim Geok
Abstract: Early assessment of malnutrition in cancer patients is very important. The Mini Nutritional Assessment (MNA) is often used to assess malnutrition in adult cancer patients. However, the diagnostic values of MNA are controversial. We aimed to analyze the diagnostic values of MNA in assessing malnutrition in adult cancer patients. A systematic search was performed using Embase, Web of Science, PubMed, the Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang Database, and China Science and Technology Journal Database (VIP). Studies comparing MNA with other tools or criteria in cancer patients were included. The quality of the included studies was assessed by the Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2). The pooled sensitivity, specificity, the area under the receiver-operating characteristic curve (AUC), and the diagnostic odds ratio (DOR) were calculated using Stata 17.0 and Meta-DiSc1.4. In addition, sensitivity, subgroup, meta-regression, and publication bias analyses were conducted. In total, 11 studies involving 1367 patients involving MNA were included. The pooled sensitivity, specificity, ROC, and DOR were 0.84 (95% CI: 0.81–0.87), 0.66 (95% CI: 0.63–0.69), 0.84 (95% CI: 0.81–0.87), and 16.11 (95% CI: 7.16–36.27), respectively. In the assessment of malnutrition in adult cancer patients, MNA has high sensitivity and moderate specificity.